An interactive and team approach to multimedia design curriculum. - Min Wu
Over the past decade, increasingly powerful technologies have made it easier to compress, distribute, and store multimedia content. The merger of computing and communications has created a ubiquitous infrastructure that brings digital multimedia closer to the users and opens up tremendous educational and commercial opportunities in multimedia content creation, delivery, rendering, and archiving for millions of users worldwide. Multimedia has become a basic skill demanded by an increasing number of potential jobs for electrical engineering/computer science graduates. In this article, the authors intend to share their experiences and new ways of thinking about curriculum development. It is beneficial for colleagues in the multimedia signal processing areas for use in developing or revising the curriculum to fit the needs and resources of their own programs.
Keywords: Curriculum development; Digital multimedia; Interactive approach; Multimedia design curriculum; Multimedia education; Multimedia learning; Multimedia signal processing; Team approach